Inactivation of Factor XIa in Vivo: Studies in Chimpanzees and in Humans - Wuillemin, Walter A; Hack, C Erik; Bleeker, Wim K; Biemond, Bart J; Levi, Marcel; Cate, Hugo ten (Thrombosis and Haemostasis, 1996)
C1-inhibitor (C1Inh), antithrombin III (ATIII), α1-antitrypsin (a1AT), and α2-antiplasmin (a2AP) are known inhibitors of factor XIa (FXIa). However, their precise contribution to FXIa inactivation in vivo is not known. We investigated FXIa inactivation in chimpanzees and assessed the contribution of these inhibitors to FXIa inactivation in patients with presumed FXI activation.Chimpanzees were infused with FXIa and the various FXIa-FXIa inhibitor complexes formed were measured. Most of FXIa was complexed to C1Inh (68%), followed by a2AP (13%), a1AT (10%), and ATIII (9%). Analysis of the plasma elimination kinetics revealed a half-life time of clearance (t1/2) for the FXIa-FXIa inhibitor complexes of 95 to 104 min, except for FXIa-a1AT, which had a t1/2 of 349 min. Due to this long t1/2, FXIa-a1AT complexes were predicted to show the highest levels in plasma samples from patients with activation of FXI. This was indeed shown in patients with disseminated intravascular coagulation, recent myocardial infarction or unstable angina pectoris. We conclude from this study that in vivo C1Inh is the predominant inhibitor of FXIa, but that FXIa-a1 AT complexes due to their relatively long t1/2 may be the best parameter to assess FXI activation in clinical samples.